1994
DOI: 10.1159/000120783
|View full text |Cite
|
Sign up to set email alerts
|

A Search for Gli Expression in Tumors of the Central Nervous System

Abstract: The gli gene was originally isolated from DNA amplified in double minutes in a glioblastoma (D259MG). Using a sensitive RNA-RNA hybridization, we tested a series of central nervous system tumors for expression of the gli gene. These included 8 glioblastoma cell lines, plus cell cultures of 5 glioblastomas, 4 anaplastic astrocytomas, 3 different ependymal tumors, a malignant menin-gioma, and a medulloblastoma. Two normal glial cell cultures were also examined. There was no gli expression in any of these specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 12 publications
0
12
1
Order By: Relevance
“…It has also been shown that mRNAs encoding elements of the SHH pathway are expressed in gliomas, and cyclopamine inhibits proliferation of glioma cell lines and gliomaspheres in vitro, as well as in orthotopic xenografts (37)(38)(39)(40). However, other studies using glioma cell lines have suggested that the SHH pathway plays a relatively minor role in gliomagenesis (41,42), and one study suggested that the SHH pathway inversely correlates with histologic malignancy (43). One potential reason for the conflicting data on the SHH pathway in gliomas could be explained in part by our demonstration that an intact tumor microenvironment or neurospheres conditions are required to maintain Gli activity, as it is down-regulated in vitro when gliomas are cultured as adherent cells with serum.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that mRNAs encoding elements of the SHH pathway are expressed in gliomas, and cyclopamine inhibits proliferation of glioma cell lines and gliomaspheres in vitro, as well as in orthotopic xenografts (37)(38)(39)(40). However, other studies using glioma cell lines have suggested that the SHH pathway plays a relatively minor role in gliomagenesis (41,42), and one study suggested that the SHH pathway inversely correlates with histologic malignancy (43). One potential reason for the conflicting data on the SHH pathway in gliomas could be explained in part by our demonstration that an intact tumor microenvironment or neurospheres conditions are required to maintain Gli activity, as it is down-regulated in vitro when gliomas are cultured as adherent cells with serum.…”
Section: Discussionmentioning
confidence: 99%
“…the plasma membrane, as demonstrated in the present report for PKC⑀. This isoform, although not typical of cells from nervous tissue (30,31), is clearly detectable in the particulate fraction of C6 rat glioma cells (31), the cell model used by Casado et al (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…However, the suggestion that amplification was important was denied shortly after [50]. Later, the HH-GLI pathway was implicated independently in familial basal-cell carcinomas (through loss of PTCH1; reviewed in Ref.…”
Section: During Development (Figure Iamentioning
confidence: 99%